Ответы и объяснения

2013-10-25T15:55:04+04:00
Tg a= cos a/sin a
tg(3p/2-4a)= cos(3p/2-4a)/ sin(3p/2-4a)
 sin(3p/2-4a)=sin(3p/2)*cos 4a-sin(4a)*cos (3p/2)=-cos 4a
 cos(3p/2-4a)=cos(3p/2)*cos 4a+sin(4a)*sin (3p/2)=-sin(4a)
tg(3p/2-4a)=-sin(4a)/-cos 4a=sin 4a/cos 4a
 tg(5p+4a)= cos(5+4a)/ sin(5p+4a)
 sin(5p+4a)=sin(5p)*cos 4a+sin(4a)*cos (5p)=-sin 4a
 cos(5p+4a)=cos(5p)*cos 4a-sin(4a)*sin (5p)=-cos(4a)
tg(5p+4a)=-cos(4a)/-sin 4a=cos 4a/sin 4a
tg(5p+4a)*tg(3p/2-4a)=(cos 4a/sin 4a)*(sin 4a/cos 4a)=1
1+2cos(3 p/2+a)=1+2*(cos(3p/2)*cos(a)-sin(3p/2)*sin(a))=
1+2*sin a
так как sin a=0.2 то 1+2*sin a=1+2*0.2=1.4